2020
DOI: 10.1016/j.jmii.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Fast track SSTI management program based on a rapid molecular test (GeneXpert® MRSA/SA SSTI) and antimicrobial stewardship

Abstract: This type of program could help adjust antibiotic treatment when inappropriate, reducing antibiotic use and costs, length of stay, CDI and related mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The dataset includes 20 different authors from Asia (n = 13), Africa (n = 5), Europe (n = 1) and America (n = 1). A total of 20 studies were included in this synthesis: seven studies employed polymerase chain reaction (PCR) for diagnosing MRSA ( 6 , 9 , 10 , 12 , 13 , 19 , 22 ), one study employed deoxyribonucleic acid (DNA) Microarray ( 7 ), two studies used DNA sequencing ( 2 , 14 ), Xpert MRSA/SA BC assay (n = 2) ( 8 , 17 ), matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF; n = 2) ( 11 , 18 ), multilocus sequence typing (MLST; n = 4) ( 15 , 20 , 23 , 24 ), GENECUBE (n = 1) ( 21 ) and staphylococcal cassette chromosome mec (SCC mec ) typing (n = 1) ( 16 ). Figure 1 is the diagrammatic flow of the study selection and list of techniques appraised in this review.…”
Section: Resultsmentioning
confidence: 99%
“…The dataset includes 20 different authors from Asia (n = 13), Africa (n = 5), Europe (n = 1) and America (n = 1). A total of 20 studies were included in this synthesis: seven studies employed polymerase chain reaction (PCR) for diagnosing MRSA ( 6 , 9 , 10 , 12 , 13 , 19 , 22 ), one study employed deoxyribonucleic acid (DNA) Microarray ( 7 ), two studies used DNA sequencing ( 2 , 14 ), Xpert MRSA/SA BC assay (n = 2) ( 8 , 17 ), matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF; n = 2) ( 11 , 18 ), multilocus sequence typing (MLST; n = 4) ( 15 , 20 , 23 , 24 ), GENECUBE (n = 1) ( 21 ) and staphylococcal cassette chromosome mec (SCC mec ) typing (n = 1) ( 16 ). Figure 1 is the diagrammatic flow of the study selection and list of techniques appraised in this review.…”
Section: Resultsmentioning
confidence: 99%
“…The extended ID and AST coverage of the RP is a major advantage in comparison to other commercially available tests, such as those based on molecular methods [6, 23–25]. MALDI-TOF MS library ensures a coverage of >2000 different species and ALFRED60AST allows antimicrobial panels customization based on user’s needs, such as the isolated pathogen, when known, or the local epidemiology.…”
Section: Discussionmentioning
confidence: 99%
“…Bouza et al evaluated the clinical impacts of a fast track SSTI/ABSSSIs management programme based on the GeneXpert assay performed directly on clinical samples 36 . This rapid molecular method can give information on whether or not S. aureus can be ruled out as a causative agent and its antimicrobial susceptibility using directly skin samples.…”
Section: Role Of the Molecular Techniquesmentioning
confidence: 99%
“…| 169 Bouza et al evaluated the clinical impacts of a fast track SSTI/ABSSSIs management programme based on the GeneXpert assay performed directly on clinical samples. 36 This rapid molecular method can give information on whether or not S. aureus can be ruled out as a causative agent and its antimicrobial susceptibility using directly skin samples. The results of this study indicated that a rapid diagnostic algorithm (Gram staining plus real-time PCR, GeneXpert MRSA/SA) for SSTI/ABSSSIs, within an antimicrobial stewardship programme, could help adjust antibiotic treatment when inappropriate, reducing antibiotic use, hospital costs, length of stay, clostridioides difficile infection and related mortality.…”
Section: The Management Of Bacterial Skin Infectionsmentioning
confidence: 99%